2023
DOI: 10.1002/tox.23754
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged exposure to the herbicide atrazine promotes kidney fibrosis by activating Wnt/β‐catenin signaling in rats

Abstract: Exposure to atrazine (ATR), a widely-used herbicide, is a potential harmful to human health due to its long-term environmental persistence and bioaccumulation. The effects of chronic exposure to ATR on renal function in rats were evaluated in this research.Female Sprague-Dawley rats at 4 weeks of age were treated with different concentrations of ATR for 6 months. No significant differences in terms of renal functions were observed after ATR treatment. In histopathological examination of the kidney, Hematoxylin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…Studies have suggested that exposure to ATR can cause mild renal cortical congestion, glomerulus inflammatory infiltration, ,, and tubular epithelial cell necrosis. , Our findings suggest that exposure to ATR leads to interstitial hemorrhage and inflammatory infiltration near the glomeruli and enlarges the cystic lumen to 3.41 and 5.83 times the original size in the A50 and A200 groups, respectively. Previous studies have shown that LYC attenuates renal cortical injury, inflammatory cell infiltration, and apoptosis, and our results suggested that LYC alleviated ATR-induced interstitial hemorrhage and inflammatory infiltration and reduced the enlarged capsular lumen by 26 and 45%, respectively.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Studies have suggested that exposure to ATR can cause mild renal cortical congestion, glomerulus inflammatory infiltration, ,, and tubular epithelial cell necrosis. , Our findings suggest that exposure to ATR leads to interstitial hemorrhage and inflammatory infiltration near the glomeruli and enlarges the cystic lumen to 3.41 and 5.83 times the original size in the A50 and A200 groups, respectively. Previous studies have shown that LYC attenuates renal cortical injury, inflammatory cell infiltration, and apoptosis, and our results suggested that LYC alleviated ATR-induced interstitial hemorrhage and inflammatory infiltration and reduced the enlarged capsular lumen by 26 and 45%, respectively.…”
Section: Discussionsupporting
confidence: 50%
“…Studies have suggested that exposure to ATR can cause mild renal cortical congestion, glomerulus inflammatory infiltration, 14,37,38 and tubular epithelial cell necrosis. 12,39 Our findings suggest that exposure to ATR leads to interstitial hemorrhage and inflammatory infiltration near the glomeruli and enlarges the cystic lumen to 3.41 and 5.83 times the original size in the A50 and A200 groups, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Wistar rats exposed to ATZ had increased renal peroxidative damage and serum uric acid levels [ 77 ]. Long-term ATZ exposure in rats caused the renal degenerative changes and fibrosis in rats [ 78 ].…”
Section: Introductionmentioning
confidence: 99%